Critical success factors in the offshore business process outsourcing of debt collection to india - Wreford, John; Pervan, Graham; Penter, K. (Centre for Global Outsourcing, 2008)
Debt collection has been an early mover in extending the traditional business process outsourcing model by using both near shore and far shore locations to source business process outsourcing services. Typically the destination of choice is a low-wage country with a plentiful supply of skilled labour. Pre-eminent in this far shore debt collection market for English-speaking countries is India. This paper describes a case study which investigates the applicability of theory from Information Systems outsourcing research in identifying the Critical Success Factors applicable to offshore business process outsourcing of debt collection to India.